Thermal Prediction Models for Virtualized Data center Servers by using Thermal-profiles - Chaudhry, Muhammad Tayyab; Chon, Chun Yong; Ling, T.C.; Rasheed, Saim; Kim, Jongwon (Malaysian Journal of Computer Science, 2016)
The energy dissipated as heat for each utilization level of a data center server is empirically measured and stored as the thermal-profile. These thermal-profiles are used to predict the outlet temperatures of the related servers for current and future utilization. The predicted outlet temperature is an important parameter for energy efficient thermal-aware workload scheduling and workload migration in green data centers. This paper presents three models for outlet temperature prediction on virtualized data center servers based on thermal-profile. The best case scenario managed to predict the outlet temperature with a negligible error of 0.3 degree Celsius.